The influence of advertising on consumers purchase decisions in malls - Wiradinata, Rangga Pratama; Sari, Siska Komala; Novianty, Astri; Moorthy, Kohbalan; Pratondo, Agus (IEEE, 2025)
It is essential to understand how advertisements influence consumer purchasing decisions to design effective marketing strategies in competitive mall environments. Although mall advertisements are common, the actual impact on consumer behavior remains under investigated. This study examines the influence of mall advertisements by classifying respondents into three classes: Not Influenced, Sometimes Influenced, and Influenced. Survey data were collected from 311 mall visitors, capturing behavioral responses across advertising related indicators. A Random Forest (RF) classification model was used to identify the most influential predictors, achieving an accuracy of 89.39%, and revealed that ad noticing frequency, ad exposure before purchase, and brand familiarity were the strongest predictors of consumer influence. These results align with theories such as familiarity heuristics and show how repeated ad exposure and brand recognition shape consumer responses. To contextualize model performance, a Decision Tree (DT) classifier was also evaluated as a baseline with 86.82% of accuracy. The findings confirm that mall advertisements play a meaningful role in shaping consumer behaviors and that RF models offer valuable insights for predicting advertisement effectiveness.